PENGARUH BOOK TAX DIFFERENCES DAN ARUS KAS TERHADAP PERSISTENSI LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI) - Dian Ariyani; Rosita Wulandari (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
Abstract This study aims to determine the effect of book tax differences and cash flow on earnings persistence. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange 2010-2015. Sampling technique in this research is done by purposive sampling method. Pursuant to purposive sampling method, sample obtained counted 24 company. The type of this research is associative research using quantitative method. The analytical method used to test the influence of book tax differences and cash flow to earnings persistence is multiple regression method with the help of software SPSS version 22. The results showed that partially, permanent differences significantly negatively affect earnings persistence, temporary differences negatively significant effect on persistence Profit, and cash flow have a significant positive effect on earnings persistence. The results of the study simultaneously show that if the permanent differences, temporary differences and cash flows have a significant effect on earnings persistence. Keywords: Permanent Differences, Temporary Differences, Cash Flow,  Earnings                    Persistence